Effectiveness of health literacy interventions on contraceptive use among women of reproductive age in rural and urban Indonesia: A systematic review - Saragih, Amaliyah Nurmely Rahmah; Damayanti, Rita (BKM Public Health and Community Medicine, 2025)
Purpose: To evaluate the effectiveness of health literacy interventions, such as health education, health promotion, and digital media use, in improving knowledge, attitudes, and contraceptive use among women of reproductive age (WRA) in Indonesia, as well as to compare outcomes in rural and urban areas. Methods: This systematic review, guided by the PRISMA 2020 framework, analyzed data from 2019 to 2024 on health literacy interventions related to contraception. Literature was sourced from four databases: Lens.org, PubMed, Scopus, and Google Scholar. Results: Out of 10,451 articles identified (Lens.org: n=1,598; PubMed: n=84; Scopus: n=121; Google Scholar: n=8,648), 154 articles were assessed for eligibility, and 22 were included in the final review. Common interventions included leaflets, videos, mobile apps, and counseling, which effectively improved WRA’s knowledge, attitudes, and contraceptive behaviors. Technology-based methods were more effective in urban areas, while community-based approaches were more effective in rural settings. Conclusion: Health literacy interventions improve contraceptive outcomes among WRA in Indonesia. Their effectiveness varies by the type of intervention and the geographic context. A combined approach of community empowerment and technology, tailored to local settings, is key to enhancing contraceptive health literacy.